A retrospective analysis on the use and wean of tracheostomy in the major trauma patient. (April 2015) - Wilson, G; Harrall, K; Burkitt, S; Emmett, S; Narula, A
Background: Major trauma affects a wide patient demographic, and tracheostomy is often required to facilitate the ventilatory wean. We wanted to identify which patients were more likely to require a tracheostomy, and how a tracheostomy affected their inpatient stay. Methods: Major trauma admissions that required intubation between 1st December 2010 and 1st August 2012 were included. Data was collected on age, pre-intubation Glasgow Coma Scale (GCS), Acute Physiology and Chronic Health Evaluation II (APACHE II) and Injury Severity Score (ISS). The inpatient course was evaluated to see how long the tracheostomy weaning process took and if the presence of a tracheostomy delayed hospital discharge. Results: In our sample of 208 patients, there was no significant difference in age, pre-intubation GCS, APACHE II, or ISS between major trauma patients who did and did not require a tracheostomy. Patients with a tracheostomy had a longer period of intubation (8.3 vs. 3.4 days) and stay in the intensive care unit (ICU; 21.4 vs. 4.5 days). Decannulation took an average of 2.7 days to achieve from the moment of first cuff deflation, which occurred 15.5 days post-tracheostomy insertion (range 1–52 days). The time from ICU discharge to hospital discharge was similar in the two groups (10.7 days with tracheostomy, 10.2 days without tracheostomy). Conclusion: Age, pre-intubation GCS, APACHE II, or ISS are predictive factors for tracheostomy in major trauma patients. Although patients with a tracheostomy had a longer period in the ICU requiring ventilation, their discharge was not otherwise delayed.